Peningkatan Kinerja Staf Desa Sumbersalak Melalui Pelatihan Dasar Microsoft Word - Fitriyah, Nur Qodariyah; Sulistyo, Henny Wahyu; Arifin, Zainul (Universitas Muhammadiyah Jember, 2023)
The partner's problem is that village officials have not been able to use some software such as Microsoft Word. The solution used to deal with problems experienced by partners is to provide training in the Microsoft Word application program. The implementation of this community service activity is on Saturday May 13 2023. The socialization activity was carried out by the proposing team more to provide motivation to village officials regarding the importance of technology, especially the Microsoft Word application, in order to expedite administrative performance in the village. Training activities are practical activities that focus on increasing the skills of village officials. Observations from the implementation of this activity provide insight into new knowledge and skills for village officials and at the same time provide benefits which of course support village administrative activities. During the implementation of the training, the enthusiasm of the village apparatus was visible both in terms of receiving the material and feedback in the form of questions. Based on observations during the activity and from several questions asked by the participants, it appears that the participants already have an idea of what Microsoft Word is and its functions and uses in village administrative activities. Participants also have additional insight and skills related to information technology, especially Microsoft Word, so that they are expected to further support village administration